Tamoxifen: An alternative to clomiphene in women with polycystic ovary syndrome - Lakhbir Kaur Dhaliwal; Vanita Suri; Kamla Rani Gupta; Sumitu Sahdev (Wolters Kluwer Medknow Publications, 2011)
Background : Clomiphene citrate is commonly used for ovulation induction in women with anovulatory infertility. However, pregnancy rates with this drug are not as good as ovulation rates. Tamoxifen may be a better choice in some patients who fail to either ovulate or conceive with clomiphene due to its favorable effect on the cervical mucus and endometrium. This study was conducted to evaluate the role of tamoxifen in women with anovulatory infertility and find out the optimum dose needed for achieving the best outcome. Materials and Methods : 160 women attending the infertility clinic and suffering from anovulatory infertility were recruited for the study. Tamoxifen was administered in the dose of 40 mg daily and ovulation monitored. In case of anovulation, the dose was increased to 80 mg daily. Ovulation and pregnancy rates were calculated. Results : Twenty-three out of 160 women who received 40 mg of tamoxifen conceived, giving a pregnancy rate of 14.38% and pregnancy rate per ovulatory cycle as 14.94%. 32 out of 80 women who received 80 mg of tamoxifen conceived, giving a pregnancy rate of 40% and pregnancy rate per cycle as 33.68%. This difference in the pregnancy rate between the two groups was statistically significant. 35 women out of 90 with polycystic ovary syndrome (PCOS) became pregnant with a pregnancy rate of 38.8% and 20 out of 70 women with clomiphene citrate failure conceived, giving a pregnancy rate of 28.5%. Conclusions : Tamoxifen is a good alternative to clomiphene in women with PCOS and clomiphene-resistant cases.